Mammals [videorecording (DVD)] - Attenborough, David, 1926- (BBC Studios, 2024)
The contemporary and unfiltered series offers fascinating insights into the most successful animal group ever, from the tiny Etruscan shrew to the giant blue whale. Mammals, the most loved group of all animals, are found on every continent and in every ocean, from the frozen wildernesses to the densest jungles, in the hottest deserts and the darkest depths. Discover the secrets to their success their winning design, incredible adaptability, unrivalled intelligence and unique sociability. The series also highlights many of the challenges facing mammals in a rapidly changing world and how they endeavour to overcome them.